Seismic behaviour of the old-type gravity load designed deteriorated RC buildings in Cyprus. (December 2017) - Safkan, Ismail; Sensoy, Serhan; Cagnan, Zehra
Abstract: Corrosion related deterioration of reinforced concrete buildings is often studied by the structural engineering community. The literature reveals the fact that modelling of deteriorated members requires a unique consideration due to brittle section behaviour. The late adaptation of seismic regulation rules and lack of decent quality construction material supply results a vulnerable building category in the island of Cyprus. This paper examines the vulnerable building category by combining concrete strength variation with different corrosion levels. A common building type representing 1980's was selected for analyses. By using the experimental data on local materials, the corrosion rate and concrete strength specific models were generated. The analyses on brittle low strength deteriorated models yielded to a reduction both in strength and ductility. The effects of considering different concrete strength on non-seismically designed deteriorated buildings were discussed herein. Highlights: Construction material statistics corresponding to pre 1992 period investigated for Northern Cyprus Advanced corrosion modelling methodology was proposed for non-ductile RC frames. Significant reduction in ultimate drift capacity is observed due to corrosion.